Quo Vadis of The Legal Standing and Ownership of A Moveable Object (Cars) Which Not Yet Fully Paid In A Perspective of Civil and Bankruptcy Law - Dian Priharyanti; Anita Afriana (Journal of Law, Politic and Humanities, 2024)
The implementation of buying and selling is often carried out on cash or credit, which often has an impact if something happens to the debtor, especially if the debtor is bankrupt. In bankruptcy, the Debtor’s asset are collateral for creditors to obtain payment of the bills that has been registered. This research will answer the question whether assets in the form of four-wheeled motorised vehicles that have not been paid in full by bankrupt debtors can be withdrawn into bankruptcy assets in bankruptcy? And when does the ownership right to a movable object transfer in a sale and purchase that overrides Article 1458 of the Civil Code with an agreement?. As for the truth in connection with these questions, the results of the discussion are obtained in the form of an explanation that motorised vehicles purchased on credit can still be part of the bankruptcy estate, even though it has not been paid in full by the debtor. As for the transfer of property rights itself, it is actually based on Article 612 of the Civil Code.